2023
DOI: 10.1007/s11357-023-00980-6
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of biological age in multiple rat organs by young porcine plasma fraction

Steve Horvath,
Kavita Singh,
Ken Raj
et al.

Abstract: Young blood plasma is known to confer beneficial effects on various organs in mice and rats. However, it was not known whether plasma from young adult pigs rejuvenates old rat tissues at the epigenetic level; whether it alters the epigenetic clock, which is a highly accurate molecular biomarker of aging. To address this question, we developed and validated six different epigenetic clocks for rat tissues that are based on DNA methylation values derived from n = 613 tissue samples. As indicated by their respecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…Therefore, the treated rats would be undergoing a significant, albeit modest, epigenetic rejuvenation. This is in line with a previous study reporting that treatment of old rats with a porcine plasma fraction markedly sets back their epigenetic age ( 9 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, the treated rats would be undergoing a significant, albeit modest, epigenetic rejuvenation. This is in line with a previous study reporting that treatment of old rats with a porcine plasma fraction markedly sets back their epigenetic age ( 9 ).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, it has been reported that treatment with human cord plasma increases synaptic plasticity and hippocampal-dependent cognition in aged mice and that one of the effectors of these improvements may be a circulating factor known as tissue inhibitor of metalloproteinases 2 ( 45 ). In old rats, there is evidence that administration of plasma proteins may exert a marked reversal of epigenetic age ( 9 ). In the present study we show, for the first time to our knowledge, that lifelong treatment of old rats with young rat plasma induces a moderate but significant epigenetic rejuvenation, extends their mean lifespan and improves the physical appearance of the animals (which, for instance, show a whither and smoother fur), an effect that might be at least in part mediated by the IGF-1/IIS system as well as homeostatic cytokine and chemokine networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood tests are used measure these factors, for example, the plasma protein signature for eleven organ-specific aging clocks (brain, muscle, artery, heart, lung, immune, liver, kidney, pancreas, adipose, intestine) to find 20% of 5,676 healthy adults already having accelerated aging in at least one organ (Oh et al 2023). Epigenetic clocks confirmed the rejuvenation of six tissues getting younger as measured by DNA methylation values (in an animal parabiosis model) (Horvath et al 2024).…”
Section: The Longevity Mindsetmentioning
confidence: 72%
“…Epigenetic clocks are a promising aging biomarker that can estimate biological age across organs based on age-related changes in DNA methylation patterns, and have demonstrated high predictive power for age-related disease onset and mortality in humans 19,20 . Epigenetic clocks have also been developed in rodents such as mice 2124 and rats 17,25 and pan-species clocks have been proposed, including human-rat pan-tissue clock 26,27 . These findings and latest studies 28 suggest that age-related changes in DNA methylation patterns are a common mechanism of aging across mammals and, simultaneously, provide a useful tool for evaluating the effectiveness of intervention strategies to delay aging in a relatively short timescale.…”
Section: Discussionmentioning
confidence: 99%